Oral antioxidant treatment partly improves integrity of human sperm DNA in infertile grade I varicocele patients. (3rd July 2015) - Gual-Frau, Josep; Abad, Carlos; Amengual, María J.; Hannaoui, Naim; Checa, Miguel A.; Ribas-Maynou, Jordi; Lozano, Iris; Nikolaou, Alexandros; Benet, Jordi; García-Peiró, Agustín; Prats, Juan
Abstract: Infertile males with varicocele have the highest percentage of sperm cells with damaged DNA, compared to other infertile groups. Antioxidant treatment is known to enhance the integrity of sperm DNA; however, there are no data on the effects in varicocele patients. We thus investigated the potential benefits of antioxidant treatment specifically in grade I varicocele males. Twenty infertile patients with grade I varicocele were given multivitamins (1500 mg L-Carnitine, 60 mg vitamin C, 20 mg coenzyme Q10, 10 mg vitamin E, 200 μg vitamin B9, 1 μg vitamin B12, 10 mg zinc, 50 μg selenium) daily for three months. Semen parameters including total sperm count, concentration, progressive motility, vitality, and morphology were determined before and after treatment. In addition, sperm DNA fragmentation and the amount of highly degraded sperm cells were analyzed by Sperm Chromatin Dispersion. After treatment, patients showed an average relative reduction of 22.1% in sperm DNA fragmentation ( p = 0.02) and had 31.3% fewer highly degraded sperm cells ( p = 0.07). Total numbers of sperm cells were increased ( p = 0.04), but other semen parameters were unaffected. These data suggest that sperm DNA integrity in grade I varicocele patients may be improved by oral antioxidant treatment.